Class Grouping of XI SMAN 1 Payaraman for the Academic Year 2023-2024 as an Implementation of Kepmendikbudristek No. 56 of 2022 - Basori, Akhmad (PPSDP International Journal of Education, 2024)
The government has implemented the Independent Curriculum since the academic year 2021–2022 in reference or superior schools. In the academic year 2022–2023, several schools have implemented the Independent Curriculum Implementation based on the BSKAP Decree concerning Educational Units Implementing the Independent Curriculum Implementation through the Independent Route in the Phase I Academic Year 2022–2023. Through this decision, SMAN 1 Payaraman became one of 8 schools in Ogan Ilir Regency that implemented an independent curriculum through the independent route in the 2022–2023 Tahaindea school year. The researcher’s aim in conducting this research was to determine the percentage of students’ interest in selected subjects provided by the school, describe the obstacles in grouping class XI study groups at SMAN 1 Payaraman according to the Independent Curriculum, and describe the strategies used. by the school in grouping class XI study groups at SMAN 1 Payaraman according to the Independent Curriculum. The data collection method used in this research was a questionnaire. The results of this research are students’ interest in the 11 subjects provided by the school, with 178 respondents. 28% chose physics, 44% chose chemistry, 74% chose biology, 47% chose advanced mathematics, 57% chose geography, 75% chose economics, 65% chose sociology, 83% chose advanced Indonesian language subjects, 58% chose advanced English, 56% chose informatics, and 44% chose entrepreneurship education. The obstacle faced is the formation of many class groups. The strategy used is to eliminate several subjects that are students’ choice.